The effects of personality and social determinants of health on sports-related concussion risk: an examination of symptom reporting, concussion incidence, and return to play - Weishaar, Megan Gardner, author; Conner, Bradley T., advisor; Prince, Mark A., committee member; Davalos, Deana B., committee member; Stephens, Jaclyn A., committee member (Colorado State University. Libraries, 2024)
Sports-related concussion (SRC), a form of mild traumatic brain injury (TBI) that occurs during sport participation or recreation, has emerged as a public health concern among adolescent athletes in the United States in recent decades due to increasing knowledge of high incidence rates. Important factors such as return to play (RTP) timeline and symptom reporting behaviors have been shown to contribute to SRC incidence. As a result, recent research has called for work that identifies a parsimonious group of variables that are salient in identifying athletes most at risk of outcomes such as early RTP, higher SRC incidence, and symptom nondisclosure. A small body of work has established that certain personality characteristics and social determinants of health are associated with these SRC outcomes. However, few specific personality and social determinants of health factors have been examined, few studies have investigated predictors of SRC incidence and RTP outcomes specifically, and a small number of these studies have investigated these research questions among adolescent athletes despite high rates of athletic participation and SRC incidence. The current study sought to expand previous work to further elucidate relations between a myriad of personality and social determinants of health predictors, and time to RTP, diagnosed SRC, and symptom reporting outcomes among adolescent athletes (N = 317, ages 14-19). The ultimate goal of the study was to identify personality and social determinants of health factors most salient in SRC outcomes to inform practical tailoring of prevention and intervention strategies. Participants were adolescents who were currently enrolled in high school or college or were enrolled in high school within the past calendar year, participated in a high school or club sport in the past year, and either denied sustaining a diagnosed SRC in the past year (N = 156) or endorsed sustaining a diagnosed SRC in the past year (N = 161). Data were collected through a one-time online survey that took participants 20-30 minutes to complete. Participants were compensated via an online gift card or course credit. Recruitment methods included outpatient medical clinics, high school athletic trainers, sports gyms and tournaments, Twitter, and university research pools. Analyses included a series of Cox proportional hazards and logistic regression models investigating associations between personality and social determinants of health predictors and time to RTP, diagnosed SRC incidence, and symptom reporting outcomes (i.e., honesty and comfort in symptom reporting). Overall, study results bolstered the conclusion that 1. Personality and social determinants of health factors are important in predicting SRC outcomes and 2. The relations between personality and SRC outcomes are highly nuanced, depending upon specific personality facets, outcome, and sample characteristics. Study results inform athletes, peers and family of athletes, coaches, athletic trainers, and other medical professionals about which personality and social determinants of health variables are most salient in SRC risk, thus informing prevention and intervention efforts for SRC such that they can be more personalized and tailored at the individual, environmental, and systems levels.
Keywords: social determinants of health; personality; sports-related concussion